2021
DOI: 10.1155/2021/5633211
|View full text |Cite
|
Sign up to set email alerts
|

WGCNA‐Based Identification of Hub Genes and Key Pathways Involved in Nonalcoholic Fatty Liver Disease

Abstract: Background. The morbidity of nonalcoholic fatty liver disease (NAFLD) has been rising, but the pathogenesis of NAFLD is still elusive. This study is aimed at determining NAFLD-related hub genes based on weighted gene coexpression network analysis (WGCNA). Methods. GSE126848 dataset based construction of coexpression networks was performed based on WGCNA. Database for Annotation, Visualization, and Integrated Discovery (DAVID) was utilized for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…WGCNA uses data from all genes to identify gene sets of interest, rather than genes only showing differential expression, and to analyze significant associations with phenotypes. WGCNA has two main advantages: i.e., loss of fewer genes and the ability to collate many genes into gene sets and identify their association with phenotypes without multiple hypothesis testing [ 40 ]. Therefore, we used WGCNA to analyze the RNA-sequencing data of Cd, salt, K, and N treatments and six dwarf mutants to identify hub genes and their target genes involved in stress adaptation and PH regulation.…”
Section: Resultsmentioning
confidence: 99%
“…WGCNA uses data from all genes to identify gene sets of interest, rather than genes only showing differential expression, and to analyze significant associations with phenotypes. WGCNA has two main advantages: i.e., loss of fewer genes and the ability to collate many genes into gene sets and identify their association with phenotypes without multiple hypothesis testing [ 40 ]. Therefore, we used WGCNA to analyze the RNA-sequencing data of Cd, salt, K, and N treatments and six dwarf mutants to identify hub genes and their target genes involved in stress adaptation and PH regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al conducted WGCNA on two datasets from GEO and identified hub genes of NAFLD ( Wu et al, 2021 ). Zeng et al used similar methods, but a different dataset to find the hub genes in NAFLD ( Zeng et al, 2021 ). Other bioinformatic tools, such as immune infiltration analysis, were also used in combination with DEG to explore the molecular mechanisms of NASH ( Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRPL27 encodes a mitochondrial ribosomal protein, and its abnormal function may cause small steric dysfunction and muscle atrophy ( Bogatikov et al, 2020 ). MRPL27 is also regarded as an NAFLD-related hub gene ( Zeng et al, 2021 ). AAR2 is a splicing factor that is a component of the U5 snRNP complex and is required for spliceosome assembly and pre-mRNA splicing ( Weber et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%